Preparation method of doped zinc oxide coated high-voltage positive electrode material
Through the preparation method of high-voltage positive electrode material doped with zinc oxide coated, the problems of structure transformation, interface side reaction and gas escape of the positive electrode material under high pressure conditions of lithium-ion batteries are solved, and the conductivity and structural stability of the material are improved. , improves the electrochemical performance and safety of the battery.
Patent Information
- Application Number
- CN202411381735.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-14
AI Technical Summary
Under high-voltage conditions, the positive electrode materials of lithium-ion batteries face problems such as structural transformation, interface side reactions and gas escape, resulting in degradation of electrochemical performance and safety threats.
Using a high-pressure positive electrode material preparation method with zinc oxide coated, the doped zinc oxide target is wrapped on the surface of the positive electrode powder by magnetron sputtering and annealing to form an ultra-thin and uniform cladding layer.
It improves the conductivity and structural stability of the positive electrode material, inhibits interfacial side reactions and gas escape, and improves the electrochemical performance and cycle life of lithium-ion batteries.
Smart Images

Figure CN119447223A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing a zinc oxide-doped high-voltage positive electrode material. Background Art
[0002] Since the commercialization of lithium-ion batteries (LIBs) in the 20th century, LIBs have become the main energy storage system for portable electronic devices and electric vehicles due to their excellent properties such as high capacity, energy density, operating voltage, safety, and long cycle life. However, the energy density of LIBs is mainly limited by the positive electrode materials. Therefore, there is an urgent need to design and optimize positive electrode materials with high capacity and working potential to improve the energy density of LIBs. Currently, transition metal layered oxides are one of the main types of positive electrode materials. This type of material includes lithium cobalt oxide (LiCoO2, LCO), ternary oxides (such as NCM and NCA), and lithium-rich oxides (Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 Although these materials have high theoretical specific capacity and working voltage, their structural stability and cycle life under high-voltage operation still present significant challenges.
[0003] Under high-voltage conditions, the main challenges faced by LIB cathode materials include: structural transformation, interfacial side reactions and gas escape. High voltage may trigger the migration of transition metals and the formation of phase changes, resulting in slow ion diffusion and increased internal resistance. At the same time, the side reactions of the electrolyte at the interface will be more intense, consuming the electrolyte and lithium ions in the active material, forming an unstable and thicker cathode electrolyte interface (CEI), thereby increasing the internal resistance. What's more serious is that the anion redox induced by high voltage will also induce oxygen (O2) and carbon dioxide (CO2). It not only affects the electrochemical performance of LIB, but also poses a threat to safety.
[0004] At present, there are two commonly used methods for modifying high-voltage positive electrode materials: one is element doping and the other is coating. Element doping mainly involves doping with various metal ions such as Al, Fe, Zn, etc. In practice, multi-element co-doping is very common, and the synergistic effect required between multiple dopants needs further exploration. Surface coating is also one of the effective methods to improve the thermal stability and structural stability of positive electrode materials. It not only improves the surface activity of the material, but also provides the material with new physical, chemical and mechanical properties. There are two main structures of surface coating materials: one is to coat the surface of the positive electrode material particles with a heterogeneous material with a thickness of several nanometers; the other is to coat different layers of different materials on the surface of the positive electrode material to form a composite material structure. Surface coating effectively inhibits the interaction between the electrode and the electrolyte, thereby improving the electrochemical performance of lithium-ion batteries.
[0005] Patent technology document CN201310612376.3 discloses a method for preparing a zinc oxide or aluminum-doped zinc oxide coated lithium cobalt oxide electrode, using zinc oxide or aluminum-doped zinc oxide as a coating material, and using a radio frequency magnetron sputtering process to deposit a zinc oxide or aluminum-doped zinc oxide film on a conventional lithium cobalt oxide electrode to obtain a coated modified lithium cobalt oxide electrode. However, directly depositing zinc oxide or aluminum-doped zinc oxide film on a lithium cobalt oxide electrode will result in a large interface resistance between lithium cobalt oxide and zinc oxide, thereby affecting the electrochemical performance of lithium-ion batteries. Summary of the invention
[0006] In view of this, the purpose of the present invention is to propose a method for preparing a high-voltage positive electrode material coated with doped zinc oxide, so as to improve the electrochemical performance of lithium-ion batteries, enhance the stability and cyclability of the positive electrode material under high voltage, and reduce interfacial side reactions and gas evolution.
[0007] Based on the above purpose, the present invention provides a method for preparing a high-voltage positive electrode material coated with doped zinc oxide. The doped zinc oxide target is first coated on the surface of the positive electrode powder by magnetron sputtering, and then annealed to obtain the high-voltage positive electrode material coated with doped zinc oxide.
[0008] Preferably, the positive electrode powder is Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 O2.
[0009] Furthermore, the doped zinc oxide target is an aluminum-doped zinc oxide target with a doping amount of 3%, and the magnetron sputtering power is 300-400 W, and the time is 1-3 h.
[0010] Furthermore, the doped zinc oxide target is a 3% aluminum-doped zinc oxide target and a 1% gallium-doped zinc oxide target, which are sequentially coated on the surface of the positive electrode powder by magnetron sputtering. The sputtering power of the 3% aluminum-doped zinc oxide target is 300 W, and the sputtering time is 1 h. The sputtering power of the 1% gallium-doped zinc oxide target is 300 W, and the sputtering time is 1 h.
[0011] Preferably, the annealing temperature is 200-400° C., the heating rate is 1-10° C. / min, the time is 1-2 h, and the atmosphere is air.
[0012] Preferably, the positive electrode powder is ball-milled to reduce its particle size before coating, the ball-milling speed is 600-800 rpm, the ball-milling time is 0.5-1 h, and the ball-to-material ratio is 5-50:1.
[0013] Beneficial effects of the present invention: (1) The coated positive electrode material prepared by the present invention has no impurity phase, the bulk lattice structure is not destroyed, the particles are fine and uniform, the coating layer is ultra-thin and uniform, and the effective surface area is increased.
[0014] (2) The zinc oxide-doped positive electrode material prepared by the present invention can improve the conductivity of the positive electrode material, avoid direct contact with the electrolyte, and inhibit side reactions between interfaces through physical isolation.
[0015] (3) The doped zinc oxide coating layer prepared by the present invention can exert a special mechanism under high voltage to regulate the anion redox reaction of the positive electrode material, inhibit gas evolution, and prevent high voltage from damaging the structure of the positive electrode material.
[0016] (4) The doped zinc oxide coated positive electrode material prepared by the present invention can form more oxygen vacancies, reduce the surface oxygen partial pressure, and inhibit oxygen evolution and oxidation side reactions of the electrolyte.
[0017] (5) The present invention provides a method for preparing a positive electrode material coated with doped zinc oxide. The method has low cost, simple operation, no pollution, high safety, and can be put into large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required to be used in the embodiments or the description of the prior art are briefly introduced below.
[0019] Figure 1 The first cycle charge and discharge curves of AZO-LRM and pristine-LRM in the present invention; Figure 2 AZO-LRM and pristine-LRM electrochemical cycle curves in the present invention; Figure 3 The electrochemical rate performance of AZO-LRM and pristine-LRM in the present invention; Figure 4 is the gas overflow amount of AZO-LRM and pristine-LRM in the present invention during the charging process; Figure 5 The XPS spectra of AZO-LRM and pristine-LRM in the present invention; Figure 6 TEM images of AZO-LRM and pristine-LRM in the present invention; Figure 7 TEM images of AZO-LRM and pristine-LRM after cycling in the present invention. DETAILED DESCRIPTION
[0020] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. Embodiment 1:
[0021] (1) Take 20g of Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 O2, ball milled at a speed of 600rpm for 30min, with a ball-to-material ratio of 30:1. After the ball milling, the powder was placed in the magnetron sputtering chamber, and magnetron sputtered using a 3% aluminum-doped AZO target. A mixed gas with a volume ratio of argon and oxygen of 3:1 was introduced, the gas pressure was 0.4Pa, the sputtering power was 300W, the sputtering time was 1h, and the drum was rotated during the sputtering process at a speed of 30rpm. After the sputtering, the product was taken out and transferred to a muffle furnace, the heating rate was 5℃ / min, and annealed at 200℃ in an air atmosphere for 1h. The resulting product was an AZO-coated lithium-rich material, named AZO-LRM-1; (2) Prepare AZO-LRM-1, carbon black Super P and PVDF into a slurry in a ratio of 8:1:1, put it into a glass bottle, and stir it magnetically for 12 hours to mix it thoroughly; (3) The positive electrode slurry is coated on the positive electrode current collector aluminum foil with a coating thickness of 300 μm, and then placed in an oven for drying. The positive electrode sheet is cut into pieces to obtain the positive electrode sheet, which is then assembled with metal lithium and polyethylene / propylene composite microporous membrane, and the electrolyte AFJ-005 provided by Envision is added to obtain a lithium-ion half-cell. Implementation 2:
[0022] (1) Take 20g of Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 O2, ball milled at a speed of 600rpm for 30min, with a ball-to-material ratio of 30:1. After the ball milling, the powder was placed in the magnetron sputtering chamber, and magnetron sputtered using a 3% aluminum-doped AZO target. A mixed gas with a volume ratio of argon and oxygen of 3:1 was introduced, the gas pressure was 0.4Pa, the sputtering power was 300W, the sputtering time was 2h, and the drum was rotated during the sputtering process at a speed of 30rpm. After the sputtering, the product was taken out and transferred to a muffle furnace, the heating rate was 5℃ / min, and annealed at 200℃ in an air atmosphere for 1h. The resulting product was an AZO-coated lithium-rich material, named AZO-LRM-2; (2) Prepare AZO-LRM-2, carbon black Super P and PVDF into a slurry in a ratio of 8:1:1, put it into a glass bottle, and stir it magnetically for 12 hours to mix it thoroughly; (3) The positive electrode slurry is coated on the positive electrode current collector aluminum foil with a coating thickness of 300 μm, and then placed in an oven for drying. The positive electrode sheet is cut into pieces to obtain the positive electrode sheet, which is then assembled with metal lithium and polyethylene / propylene composite microporous membrane, and the electrolyte AFJ-005 provided by Envision is added to obtain a lithium-ion half-cell. Implementation 3:
[0023] (1) Take 20g of Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 O2, ball milled at a speed of 600rpm for 30min, with a ball-to-material ratio of 30:1. After the ball milling, the powder was placed in the magnetron sputtering chamber, and magnetron sputtered using a 3% aluminum-doped AZO target. A mixed gas with a volume ratio of argon and oxygen of 3:1 was introduced, the gas pressure was 0.4Pa, the sputtering power was 300W, the sputtering time was 3h, and the drum was rotated during the sputtering process at a speed of 30rpm. After the sputtering, the product was taken out and transferred to a muffle furnace, the heating rate was 5℃ / min, and annealed at 200℃ in an air atmosphere for 1h. The resulting product was an AZO-coated lithium-rich material, named AZO-LRM-3; (2) Prepare AZO-LRM-3, carbon black Super P and PVDF into a slurry in a ratio of 8:1:1, put it into a glass bottle, and stir it magnetically for 12 hours to mix it thoroughly; (3) The positive electrode slurry is coated on the positive electrode current collector aluminum foil with a coating thickness of 300 μm, and then placed in an oven for drying. The positive electrode sheet is cut into pieces to obtain the positive electrode sheet, which is then assembled with metal lithium and polyethylene / propylene composite microporous membrane, and the electrolyte AFJ-005 provided by Envision is added to obtain a lithium-ion half-cell. Embodiment 4:
[0024] (1) Take 20g of Li 1.2 Ni 0.133 Co 0.133 Mn 0.544O2, ball milling for 30 minutes at a speed of 600rpm, the ball-to-material ratio is 30:1, after the ball milling, the powder is placed in the magnetron sputtering chamber, and magnetron sputtering is performed using a 3% aluminum-doped AZO target, and a mixed gas with a volume ratio of 3:1 of argon and oxygen is introduced, the pressure is 0.4Pa, the sputtering power is 300W, and the sputtering time is 1h. Then the 3% aluminum-doped AZO target is replaced with a 1% gallium-doped GZO target, and a mixed gas with a volume ratio of 3:1 of argon and oxygen is introduced, the pressure is 0.4Pa, the sputtering power is 300W, and the sputtering time is 1h. During the entire sputtering process, the drum is rotated at a speed of 30rpm. After the sputtering is completed, the product is taken out and transferred to a muffle furnace, the heating rate is 5℃ / min, and annealed at 200℃ in an air atmosphere for 1h. The resulting product is a lithium-rich material coated with GZO and AZO, named GAZO-LRM; (2) GAZO-LRM, carbon black Super P and PVDF were prepared into a slurry in a ratio of 8:1:1, placed in a glass bottle, and magnetically stirred for 12 h to mix thoroughly; (3) The positive electrode slurry is coated on the positive electrode current collector aluminum foil with a coating thickness of 300 μm, and then placed in an oven for drying. The positive electrode sheet is cut into pieces to obtain the positive electrode sheet, which is then assembled with metal lithium and polyethylene / propylene composite microporous membrane, and the electrolyte AFJ-005 provided by Envision is added to obtain a lithium-ion half-cell.
[0025] Comparative Example 1: Take 20g of Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 O2, ball milled at a speed of 600rpm for 30min, with a ball-to-material ratio of 30:1. The uncoated lithium-rich material after grinding was named pristine LRM. Pristine LRM, carbon black Super P, and PVDF were configured into slurry in a ratio of 8:1:1, put into a glass bottle, and magnetically stirred for 12h to fully mix. The above-mentioned positive electrode slurry was coated on the positive electrode current collector aluminum foil with a coating thickness of 300μm, and then placed in an oven for drying. The positive electrode sheet was obtained after cutting, and then assembled with metal lithium and polyethylene / propylene composite microporous membrane, and the electrolyte AFJ-005 provided by Vision Company was added to obtain a lithium-ion half-cell.
[0026] Comparative Example 2: (1) Take 20g of Li 1.2 Ni 0.133 Co 0.133 Mn 0.544O2, ball milled at a speed of 600rpm for 30min, with a ball-to-material ratio of 30:1. The uncoated lithium-rich material after grinding was named pristine LRM. Pristine LRM, carbon black Super P, and PVDF were configured into slurry according to a ratio of 8:1:1, put into a glass bottle, and magnetically stirred for 12h to fully mix. Then, the above positive electrode slurry was coated on the positive electrode current collector aluminum foil with a coating thickness of 300μm, and then placed in an oven for drying, and the positive electrode sheet was obtained after cutting; (2) The positive electrode piece was installed in the magnetron sputtering chamber, and the AZO target material with a 3% aluminum doping amount was used for magnetron sputtering. A mixed gas with a volume ratio of argon and oxygen of 3:1 was introduced, the gas pressure was 0.4 Pa, the sputtering power was 300 W, and the sputtering time was 2 h. After the sputtering was completed, the product was taken out and transferred to a muffle furnace. The heating rate was 5 °C / min, and annealed at 200 °C in an air atmosphere for 1 h. The obtained product was the AZO-coated positive electrode piece; (3) The AZO-coated positive electrode sheet and the metallic lithium were assembled with a polyethylene / propylene composite microporous membrane, and the electrolyte AFJ-005 provided by Envision was added to prepare a lithium-ion half-cell.
[0027] Comparative Example 3: (1) Take 20g of Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 O2, ball milling for 30 minutes at a speed of 600rpm, the ball-to-material ratio is 30:1, after the ball milling, the powder is placed in the magnetron sputtering chamber, and a 1% gallium-doped GZO target is used for magnetron sputtering, and a mixed gas with a volume ratio of 3:1 of argon and oxygen is introduced, the gas pressure is 0.4Pa, the sputtering power is 300W, and the sputtering time is 1h. Then the AZO target with a 1% gallium doping amount is replaced with an AZO target with a 3% aluminum doping amount, and a mixed gas with a volume ratio of 3:1 of argon and oxygen is introduced, the gas pressure is 0.4Pa, the sputtering power is 300W, and the sputtering time is 1h. The drum is rotated during the whole sputtering process, and the speed of the drum is 30rpm. After the sputtering is completed, the product is taken out and transferred to a muffle furnace, the heating rate is 5℃ / min, and annealed at 200℃ in an air atmosphere for 1h. The obtained product is a lithium-rich material coated with GZO and AZO, named AGZO-LRM; (2) Prepare AGZO-LRM, carbon black Super P and PVDF into a slurry in a ratio of 8:1:1, put it into a glass bottle, and stir it magnetically for 12 hours to mix it thoroughly; (3) The positive electrode slurry is coated on the positive electrode current collector aluminum foil with a coating thickness of 300 μm, and then placed in an oven for drying. The positive electrode sheet is cut into pieces to obtain the positive electrode sheet, which is then assembled with metal lithium and polyethylene / propylene composite microporous membrane, and the electrolyte AFJ-005 provided by Envision is added to obtain a lithium-ion half-cell.
[0028] The lithium ion half-cells prepared in the examples and comparative examples were subjected to the first charge and discharge cycle test, and the results are shown in Table 1; sample Cut-off voltage / V mechanism Charging capacity / mAh / g Discharge specific capacity / mAh / g Coulomb efficiency / % Example 1 4.8 Constant current 0.1C 330.4 258.6 78.27 Example 2 4.8 Constant current 0.1C 322.0 262.7 81.58 Example 3 4.8 Constant current 0.1C 320.6 249.6 77.85 Example 4 4.8 Constant current 0.1C 318.1 270.2 84.94 Comparative Example 1 4.8 Constant current 0.1C 343.2 250.7 73.05 Comparative Example 2 4.8 Constant current 0.1C 328.5 247.4 75.31 Comparative Example 3 4.8 Constant current 0.1C 336.5 241.6 76.33 According to the results of Examples 1-4 and Comparative Example 1 in Table 1, it can be found that the first cycle charge capacity of the pristine-LRM in Comparative Example 1 is 343.2 mAh / g, the discharge capacity is 161.4 mAh / g, and the coulombic efficiency is 73.05%. All prepared by this method have improved coulombic efficiency. The AZO-LRM prepared in Example 2 in the single sputtering coating has the best effect, the first cycle charge capacity is reduced to 322.0 mAh / g, the discharge capacity reaches 262.7 mAh / g, and the coulombic efficiency is increased to 81.58%. The double sputtering coating can further improve the coulombic efficiency to 86.58%, which may be due to the solid solution formed by the aluminum-doped zinc oxide with a smaller atomic radius in the inner layer of the double sputtering coating and the positive electrode material, which helps to reduce the interface resistance, and the rich oxygen vacancies formed by the gallium-doped zinc oxide with a larger atomic radius in the outer layer help to reduce the surface oxygen partial pressure, inhibit oxygen precipitation and oxidation side reactions of the electrolyte, and the gradient doping formed by the inner and outer layers can improve the lithium ion conductivity and electron mobility.
[0029] From the results of Example 2 and Comparative Example 2 in Table 1, it can be found that, compared with directly sputtering the AZO coating on the surface of the prepared positive electrode plate, the lithium ion half-cell obtained by the preparation method of the present invention has significantly improved coulombic efficiency, which is improved by 8.3%. This is mainly due to the high interface resistance of sputtering the AZO coating directly on the positive electrode plate, while AZO is first sputtered onto the surface of the positive electrode powder and then subjected to heat treatment, a solid solution is generated at the interface between AZO and the powder, which is conducive to the transmission of lithium ions, thereby improving the coulombic efficiency.
[0030] From the results of Example 2 and Comparative Example 3 in Table 1, it can be found that the order of double sputtering coating is crucial, and the coulombic efficiency of the lithium ion half-cell prepared by inner layer aluminum doping and outer layer gallium doping is higher than that of the lithium ion half-cell prepared by inner layer gallium doping and outer layer aluminum doping.
[0031] pass Figure 2 The electrochemical cycling curves of AZO-LRM and pristine-LRM show that the capacity of pristine LRM decreases to 106.4 mAh g after 200 cycles at 0.5C. -1The capacity retention rate is 52.37%, while AZO-LRM has a significant capacity improvement. The best performing AZO-2 has a capacity of 198.5 mAh g after 200 cycles. -1 The capacity retention rate is still 91%. AZO-1 and AZO-3 can also maintain about 80% of the capacity after 100 cycles.
[0032] pass Figure 3 The electrochemical rate performance of AZO-LRM and pristine-LRM shows that the capacity of the three AZO-LRMs is improved under various current density conditions, and the capacity improvement increases with the increase of current density. The rate performance of AZO-2 is the most obvious, increasing to 176 and 145 mAh·g at 2C and 5C rates, respectively. -1 AZO-1 is second, and AZO-3 is because the impedance increases due to the excess, but the rate performance is still improved compared to the pristine LRM. As a conductive oxide, AZO can accelerate the electron conduction rate, thereby increasing the capacity under high current. After cycling at different rates, when it returns to 0.1C, the capacity does not change, which shows the stability of the lithium-rich material to current after coating.
[0033] pass Figure 4 From the gas overflow of AZO-LRM and pristine-LRM during the charging process, it can be seen that during the charging process at a rate of 0.1C, pristine LRM began to generate oxygen at 4.55V, and the oxygen generation rate continued to increase with the subsequent charging process. No obvious oxygen generation was detected in the AZO-LRM during the first cycle of charging. This shows that the constructed AZO layer can inhibit the overflow of oxygen. In the process of oxygen generation, O n- These substances will react with the EC / DMC of the electrolyte, decomposing the electrolyte and producing CO2. Pristine LRM produces CO2 at 4.5V, and the generation rate increases rapidly and then reaches a maximum. In contrast, the CO2 generation rate of AZO-LRM is significantly reduced, about 2 / 5 of that of pristine-LRM. This can directly indicate that the AZO coating can reduce the reaction between the electrode and the electrolyte, and help to construct an interface layer with excellent performance.
[0034] pass Figure 5 The XPS spectra of AZO-LRM and pristine-LRM show that AZO-LRM shows Zn 2p and Al 2p, which are not found in pristine LRM. 2+ and Al 3+ The signal further proves the successful coating of AZO.
[0035] pass Figure 6 From the TEM images of AZO-LRM and pristine-LRM, it can be seen that clear layered structure stripes can be seen in the TEM images of pristine LRM and AZO-LRM, and the crystal plane spacing is 0.479nm, corresponding to the 003 crystal plane of the layered structure, while in AZO-LRM, a coating layer of about 3nm thick can be seen on the surface of the particles.
[0036] pass Figure 7 From the TEM images of AZO-LRM and pristine-LRM after cycling, we can see that in the HRTEM image, pristine LRM and AZO-LRM show completely different properties. After cycling, pristine LRM has a very thick and irregular interface layer, about 16 nm thick. The LRM surface next to the interface layer is a spinel structure material with a crystal plane spacing of 0.309 nm, which is consistent with (112) spinel. On the inner side is a layered structure, and stripes with severe collapse and deformation can be seen, indicating that even the internal layered structure has been damaged to a considerable extent. Similarly, when observing AZO-LRM, a complete layered structure and a thin and uniform interface layer can be seen, and no spinel phase is observed. Through TEM, we can directly observe the reason why AZO-LRM has higher cycle performance. The thick interface layer and damaged layered structure of pristine LRM lead to high impedance and low lithium ion pass rate of pristine LRM.
[0037] The above results show that the thickness of the doped ZnO coating has a significant effect on the performance, and also show that the method of the present invention can accurately control the coating thickness. The positive electrode material coated with doped ZnO can significantly reduce the precipitation of gas, especially oxygen. Similarly, the serious interfacial side reactions under high pressure are also significantly reduced, preventing the increase in impedance due to the thickening of the interface layer.
[0038] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A method for preparing a high-voltage positive electrode material coated with doped zinc oxide, characterized in that: First, a doped zinc oxide target is coated on the surface of the positive electrode powder by magnetron sputtering, and then annealed to obtain a high-voltage positive electrode material coated with doped zinc oxide; The positive electrode powder is Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 O2.
2. The method for preparing a high voltage positive electrode material coated with doped zinc oxide according to claim 1, characterized in that: The doped zinc oxide target is an aluminum-doped zinc oxide target with a doping amount of 3%, and the magnetron sputtering power is 300-400 W, and the time is 1-3 hours.
3. The method for preparing a high voltage positive electrode material coated with doped zinc oxide according to claim 1, characterized in that: The doped zinc oxide target is an aluminum-doped zinc oxide target with a doping amount of 3% and a gallium-doped zinc oxide target with a doping amount of 1%, which are wrapped on the surface of the positive electrode powder in this order by magnetron sputtering. The sputtering power of the aluminum-doped zinc oxide target with a doping amount of 3% is 300W, and the sputtering time is 1h. The sputtering power of the gallium-doped zinc oxide target with a doping amount of 1% is 300W, and the sputtering time is 1h.
4. The method for preparing a high voltage positive electrode material coated with doped zinc oxide according to claim 1, characterized in that: The annealing temperature is 200-400° C., the heating rate is 1-10° C. / min, the time is 1-2 h, and the atmosphere is air.
5. The method for preparing a high voltage positive electrode material coated with doped zinc oxide according to claim 1, characterized in that: The positive electrode powder is ball-milled to reduce the particle size before coating, the ball-milling speed is 600-800 rpm, the ball-milling time is 0.5-1 h, and the ball-to-material ratio is 5-50:1.
Citation Information
Patent Citations
Making method of zinc oxide or aluminum-doped zinc oxide coated lithium cobaltate electrode
CN103594684A